A sustainability assessment method for greenfields, low cost, cement block housing developments on the Cape Flats - Walker, Jeanette (University of Cape Town, 2016)
Bibliography: pages 107-112. === This dissertation describes the development and pilot application of a sustainability assessment method for greenfields, low cost, cement block housing developments on the Cape Flats. The aim of this assessment method is to provide a means for assessing the sustainability of these low cost housing developments. The sustainability assessment method was developed within the theoretical parameters of sustainable development and sustainable construction. Literature relating to sustainable development, sustainable construction, green building and low cost housing was reviewed for this dissertation. Thirty-two persons involved in low cost housing were consulted during this study. Seven greenfields low cost housing projects on the Cape Flats were investigated. The sustainability assessment method was applied to two case studies in order to assess the sustainability of these two projects and to establish whether the method is a workable assessment tool. The sustainability assessment method includes three categories, namely technical, biophysical and socio-economic factors of sustainability. Technical factors are focused on the most in this study followed by biophysical and then socio-economic factors. Technical sustainability has been neglected in the sector of low cost housing, and is of pivotal importance in terms of achieving the overall sustainability of these housing projects. Technical factors of sustainability, such as external coating, ceilings and mortar mix, performed poorly in the assessment. Certain factors relating to biophysical sustainability, especially the efficient use of water and energy, were weak. A socio-economic factor in need of attention is the education and training of beneficiaries of houses around sustainable living practices. Recommendations are made regarding improving the sustainability of greenfields, low cost housing projects on the Cape Flats. It was concluded in this study that the sustainability assessment method is a feasible assessment tool which should be further tested and refined in the field.